Extending the application of bifunctional ionic liquid-based integrated capture and conversion of CO2 to produce cyclic carbonates - Belinchón, Alejandro; Pereira, Álvaro; Hernández, Elisa; Navarro, Pablo; Palomar, José (Journal of CO2 utilization, 2024)
Nowadays there is an urgent need for mitigating CO2 emissions through clean energy and the development of new carbon capture and utilization (CCU) technologies. Among others, the use of bifunctional ionic liquids (ILs) addressed simultaneously CO2 capture and conversion steps, having applied successfully to the propylene carbonate production case. In this work, a systematic evaluation of all representative cyclic carbonate literature was made, covering ethylene, propylene, butylene, hexylene, cyclohexene, and styrene cyclic carbonates, in order to guide the product role within the integrated CCU (ICCU) concept. The multiscale strategy combining molecular simulation (DFT -Density Functional Theory-, COSMO -COnductor-like Screening MOdel-), process simulation (COSMO/Aspen methodology), and life cycle assessment (LCA) was used to set up, simulate and evaluate the processes. ICCU configuration is the best approach when compared with sequential configuration for energy consumption analysis (reduction of 28, 28, 22, 11 and 6 %, respectively, for ethylene, propylene, butylene, hexylene, and cyclohexene cases) and CO2 emissions associated (reduction of 38, 40, 31 and 14 %, respectively, for ethylene, propylene, butylene, and hexylene cases). The main variable of the results is the boiling point of the cyclic carbonate since heavy products impose technical limitations and even discard ICCU alternative. The ICCU concept works since all cyclic carbonates’ reaction enthalpies are higher than that of the IL-CO2 one, which reduces heating requirements. Finally, energy demand can be slightly further reduced, partially recycling the cyclic carbonate to the capture unit. [Display omitted] •Sequential and integrated CO2 capture and conversion processes were evaluated.•Integrated schemes are better in energy consumption in almost all the cases.•Neat emissions are highly improved in integrated processes.•Product’s boiling point was found to be the optimization key in all scenarios.